2012
DOI: 10.1002/jcp.23051
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of angiogenin in stress response and cell survival under adverse conditions

Abstract: Angiogenin (ANG), also known as ribonuclease (RNASE) 5, is a member of the vertebrate-specific, secreted RNASE superfamily. ANG was originally identified as a tumor angiogenic factor, but its biological activity has been extended from inducing angiogenesis to stimulating cell proliferation and more recently, to promoting cell survival. Under growth conditions, ANG is translocated to nucleus where it accumulates in nucleolus and stimulates ribosomal RNA (rRNA) transcription, thus facilitating cell growth and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
131
1
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(144 citation statements)
references
References 59 publications
6
131
1
6
Order By: Relevance
“…However, it is not a general stress response; tRNA cleavage was not observed in ␥-irradiated (4), etoposide-treated, or caffeine-treated human cells (5). Several groups have studied the mechanism of ANG-induced tRNA cleavage (12). The general consensus is that during some stress conditions, ANG-induced tRNA cleavage is either (a) activated by the translocation of ANG into the cytoplasm from the nucleus, thus bringing it into the proximity of its substrates or (b) activated by disassociation of ANG from its cytoplasmic inhibitor ribonuclease/angiogenin inhibitor 1 (RNH1), thus activating its RNase activity (6).…”
Section: Ang-induced Trna Cleavage In Mammalian Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is not a general stress response; tRNA cleavage was not observed in ␥-irradiated (4), etoposide-treated, or caffeine-treated human cells (5). Several groups have studied the mechanism of ANG-induced tRNA cleavage (12). The general consensus is that during some stress conditions, ANG-induced tRNA cleavage is either (a) activated by the translocation of ANG into the cytoplasm from the nucleus, thus bringing it into the proximity of its substrates or (b) activated by disassociation of ANG from its cytoplasmic inhibitor ribonuclease/angiogenin inhibitor 1 (RNH1), thus activating its RNase activity (6).…”
Section: Ang-induced Trna Cleavage In Mammalian Cellsmentioning
confidence: 99%
“…However, it is not known whether increases in tRNA levels in transformed cells lead to increases in tRNA fragments. Because ANG level is upregulated in several kinds of cancer, it is possible that ANGinduced tRNA halves might be enriched in these scenarios (12,52). Two recent studies have revealed that endogenous tRNA fragments can play important roles in breast cancer and prostate cancer etiology.…”
Section: Tirnas In Human Biology and Disease Etiologymentioning
confidence: 99%
“…ANG also facilitates the production of tiRNA (tRNA-derived stress induced RNA) [8,9] which suppress overall protein translation. tiRNA is important in stress mechanisms under adverse environments utilized by cell [10]. ANG and RNASE4 transcription is regulated by RNA polymerase III and a CCCTC binding factor (CTCF)-depending intragenic chromatin loop [11].…”
Section: Introductionmentioning
confidence: 99%
“…In turn, tiRNAs repress global translation by interfering with translation initiation factors, but specifically facilitate the translation of mRNA that contains internal ribosomal entry sites (IRES) (3)(4)(5). Since numerous IRES-containing mRNAs encode pro-survival and anti-apoptotic genes, angiogenin protects cells from apoptosis during cell stress (6,7). In addition, the direct interaction of angiogenin with p53 (8), and interaction between tiRNAs and cytochrome c released from the mitochondria (9), have been detected to inhibit cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…The number of PBMCs, from each of the two individuals that contribute to the formation of an MLR couple, was 5x10 5 cells, measuring 1x10 6 PBMCs per well. Resting PMBC cultures of 1x10 6 cells per well from each member of the MLR couple were used as controls.…”
Section: Introductionmentioning
confidence: 99%